Nocturnal Asthma: A Special Type of Asthma - Jiang Xiongbin (Global Journal of Allergy - Peertechz Publications, 2016)
Nocturnal asthma is defined by a drop in forced expiratory volume in 1 second (FEV1) of at least 15% between bedtime and awakening in patients with clinical and physiologic evidence of asthma. Nocturnal asthma is associated with a circadian pattern in lung function, distal airway inflammation, glucocorticoid receptor affinity, pulmonary capillary blood volume, and beta-2 adrenergic receptor function may also contribute. Knowledge of these characteristics, along with an understanding of the specific therapies directed at the circadian nature of this disease, can result in significant improvements in lung function, sleep quality, and asthma related quality of life.